The Spiritual and Socio-Educational Implications of Geojassi Christian School - Jun-Ki Chung (Pharos Journal of Theology)
The study of spiritual and socio-educational contexts becomes an important component in the transformation of the educational environment, where the emphasis shifts from academic learning to the formation of personality, reflecting the current trends focused on the comprehensive development of students. The study aims to analyse the features of pedagogical approach in Korean education using Geojassi School as a case study. To achieve the research objectives, the following methods were used: deductive, axiomatic, comparative. The results indicated that religious principles are successfully integrated into the pedagogical approach of the Korean educational paradigm, actively contributing to the formation of appropriate character and values of students. Worship services, participation in prayer practices, charitable initiatives, and religious rituals influence the creation of Christian beliefs as well as reinforce moral values and promote spiritual abilities. This approach of Korean education is actively transformed within Korean secondary education, emphasizing the importance of social responsibility. In turn, the study noted that educational institutions face several obstacles, the most notable of which are excessive tuition rates and conflicts between teachers and students or parents. However, Christian schools are able to cope with these challenges by focusing on the spiritual development of students. In particular, Geojassi Christian School not only prepares students for the challenges of modern society but also instils in them an unbreakable foundation of leadership values that is evident in every aspect of their lives through the mentorship of teachers. The results of the study can be used to optimize educational practices and adapt successful methods of spiritual and socio-educational influence within educational institutions.